1998
DOI: 10.1073/pnas.95.12.6774
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral agent blocks breathing of the common cold virus

Abstract: A dynamic capsid is critical to the events that shape the viral life cycle; events such as cell attachment, cell entry, and nucleic acid release demand a highly mobile viral surface. Protein mass mapping of the common cold virus, human rhinovirus 14 (HRV14), revealed both viral structural dynamics and the inhibition of such dynamics with an antiviral agent, WIN 52084. Viral capsid digestion fragments resulting from proteolytic time-course experiments provided structural information in good agreement with the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
238
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(258 citation statements)
references
References 20 publications
13
238
0
2
Order By: Relevance
“…Most antibodies generated to RV infection in humans are directed against epitopes found on surface-exposed structures of VP1, VP2 and VP3 (Carey et al, 1992). Although there is evidence that the N-terminus of VP4 may be transiently exposed at the capsid surface in a process known as capsid breathing (Lewis et al, 1998) and antibodies to this region of VP4 are cross-serotype protective (Katpally et al, 2009), naturally occurring human antibodies to VP4 have not been described. A recent study by Niespodziana et al revealed that children with RV-induced respiratory symptoms primarily generate IgG1 and IgA to N-terminal regions of VP1 and that responses to VP2, VP3 and VP4 were significantly lower .…”
Section: Discussionmentioning
confidence: 99%
“…Most antibodies generated to RV infection in humans are directed against epitopes found on surface-exposed structures of VP1, VP2 and VP3 (Carey et al, 1992). Although there is evidence that the N-terminus of VP4 may be transiently exposed at the capsid surface in a process known as capsid breathing (Lewis et al, 1998) and antibodies to this region of VP4 are cross-serotype protective (Katpally et al, 2009), naturally occurring human antibodies to VP4 have not been described. A recent study by Niespodziana et al revealed that children with RV-induced respiratory symptoms primarily generate IgG1 and IgA to N-terminal regions of VP1 and that responses to VP2, VP3 and VP4 were significantly lower .…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism involves the modification of proteins, which would cause inhibition of viral cell entry or the release of the genome. The second mechanism allows the alkylating reagents direct access to the viral genome through a mobile protein capsid (8)(9)(10)(11)(12). The recent findings (8)(9)(10)(11) that the protein capsids of viruses in solution have a much higher degree of dynamics than their crystallized counterparts suggested that the second mechanism might be the means of inactivation.…”
mentioning
confidence: 99%
“…The second mechanism allows the alkylating reagents direct access to the viral genome through a mobile protein capsid (8)(9)(10)(11)(12). The recent findings (8)(9)(10)(11) that the protein capsids of viruses in solution have a much higher degree of dynamics than their crystallized counterparts suggested that the second mechanism might be the means of inactivation. Focusing on this latter idea, the ability of small alkylating agents to react with either the capsid or encapsidated nucleic acid was investigated initially by using flock house virus (FHV), an RNA-containing model virus used in previous studies (8,9).…”
mentioning
confidence: 99%
“…A further complication for RVs is that the aforementioned NIms are largely serotype specific and that highly conserved capsid epitopes are not normally surface exposed and therefore unavailable for conventional Ab binding. Nevertheless, sequence conservation is found at the N terminus of the buried capsid protein VP4, which is transiently exposed at the surface in a process known as capsid breathing [5], and polyclonal Abs to this region are cross-serotype protective in vitro [14]. Such rare Abs may be worth further investigation as potential prophylactics, as are those Abs with the ability to interact with the conserved residues found deep in the capsid canyon -the site of ICAM-1 binding for major group RVs.…”
Section: Prophylactic Antibodies For Rhinovirusesmentioning
confidence: 99%
“…Nevertheless, several Abs (approximately 10 of 200) are undergoing preclinical development or are in clinical trials for viral infectious diseases targets including HIV-1, HBV, human rhinoviruses (RV) and human cytomegalovirus [3]. RV may be particularly suited to the application of prophylactic Abs as no appropriate antiviral therapies are available despite numerous attempts [5][6][7], vaccine development faces challenging obstacles [8,9] and new information regarding protective antibody responses is being unearthed [10][11][12][13][14]. Thus, a full evaluation of the application of prophylactic Abs to these important human pathogens where there is an explicit need for appropriate therapeutic/ prophylactic interventions is warranted.…”
mentioning
confidence: 99%